2002
DOI: 10.1080/0268869021000007623
|View full text |Cite
|
Sign up to set email alerts
|

Home-made gun injury: spontaneous version and anterior migration of bullet

Abstract: We report a unique case of a self-inflicted brain injury using an ingenious home-made gun with spontaneous anterior migration of the intact bullet. On admission, the patient was fully conscious with no neurological deficits. Computed tomography (CT) confirmed a penetrating missile injury with transventricular across midline trajectory and multi-lobe injury with the bullet lodged in the occipital lobe. Serial CT revealed spontaneous version with anterior migration of the bullet from the occipital lobe to finall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 8 publications
2
7
0
Order By: Relevance
“…[8] Similarly, many other successfully managed cases of PBI have been reported from Africa. [2283538] Our case further corroborates the notion that the multiple limitations of neurosurgical practice in an African nation do not prevent the successful management of select cases of penetrating head trauma. [8]…”
Section: Discussionsupporting
confidence: 71%
“…[8] Similarly, many other successfully managed cases of PBI have been reported from Africa. [2283538] Our case further corroborates the notion that the multiple limitations of neurosurgical practice in an African nation do not prevent the successful management of select cases of penetrating head trauma. [8]…”
Section: Discussionsupporting
confidence: 71%
“…Interestingly enough, the orientation of the bullet remained unchanged. G.Alessi et al have described spontaneous version and anterior migration of the bullet again with the orientation of the bullet remaining unchanged 8 . Ross D et al have reported two cases of spontaneous migration of retained bullets 9 .…”
Section: Discussionmentioning
confidence: 99%
“…The literature (1)(2)(3)(4)(5)(6)(7)(8) shows that persons using home-made guns to commit suicide were exclusively men. Women who commit suicide with a firearm typically use guns of serial production.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, cases in which a home‐made firearm is used to perform an intended suicide are very rare. The literature describes only tens of such cases by means of these unusual firearms (1–8). Unfortunate accidents (9,10) and homicides (11,12) are extremely uncommon.…”
mentioning
confidence: 99%